Mixed functionalization strategy on indium-organic framework for multiple ion detection and H2O2 turn-on sensing. Issue 22 (11th May 2021) - Jiang, Xin; Fan, Ruiqing; Zhou, Xuesong; Zhu, Ke; Sun, Tiancheng; Zheng, Xubin; Xing, Kai; Chen, Wei; Yang, Yulin
Abstract : A mixed-functionalization strategy on In-MOF realizes high sensitivity detection of heavy metal ions, anions and small molecules. Abstract : A special functional group mediated functionalization platform is introduced as a new and versatile platform tool to improve the fluorescence detection performance of metal–organic frameworks (MOF). The creation of a mixed-functionalization strategy on a MOF realizes the high sensitivity detection of heavy metal ions, anions and small molecules. In this work, we have first reported a novel amino functionalized 3D indium MOF [In(BDC-NH2 )(OH)] n (In1-NH2 ) which not only has an excellent fluorescent characteristic but also shows highly sensitive identification of Fe 3+, Cu 2+, Pb 2+ and ClO − in water with broad linear ranges and short response times. Subsequently, based on the remaining amino group site of In1-NH2, a post-synthetic modification strategy is utilized to introduce an active boronic acid group for hydrogen peroxide detection. The obtained PBA-In1 exhibits an efficient sensing performance for hydrogen peroxide with an LOD of 0.42 μM. Given this, PBA-In1 is expected to become an effective probe to monitor the formation of metabolites in humans. In1-NH2 successfully achieves multiple ion detection and the PBA-In1 sensing platform with boronic acid functionalization may have good application prospects in biochemical research in the future.